A photo-capacitive sensor operational from 6 K to 350 K with a solution printable, thermally-robust hexagonal boron nitride (h-BN) dielectric and conductive graphene electrodes. (September 2020) - Desai, Jay A.; Bandyopadhyay, Avra; Min, Misook; Saenz, Gustavo; Kaul, Anupama B.
Highlights: Temperature-dependent Raman measurements on ink-jet printed h-BN films yields an empirically determined first-order temperature coefficient χ which is very low, revealing the thermally robust nature of the ink jet printed h-BN. All-inkjet-printed graphene/h-BN/graphene capacitors were fabricated and the leakage current density was measured to be low. Optical illumination on the graphene/h-BN/graphene heterostructures enabled us to reveal a novel photo-capacitive nature for our trilayer structures over a wide range of temperatures from 6 K to 350 K. Abstract: A new exfoliation route is introduced for overcoming the drawback of horn-tip exfoliation by combining it with slow magnetic stirring for hexagonal boron nitride (h-BN) bulk crystals. Inkjet printing of h-BN is then conducted, where various patterns were designed and printed and a change from translucent-to-opaque was observed with increasing printing passes from 1 pass (0.417 µm thickness) to 5 passes (1.964 µm thickness). The increase in the E2g peak intensity in the Raman spectra with the thickness of h-BN printed films is demonstrated, which is attributed to an increase in collective photon number as thickness increases. The effect of temperature on the Raman spectra of printed h-BN patterns is studied and the first-order temperature coefficient χ is derived indicative of the thermal properties of printed h-BN films at elevated temperatures. The red-shift of the E2g peak with temperature arises from the variation in the interplanar vibrational frequency with material expansion due to heating. The χ values of −0.033 cm −1 /K and −0.028 cm −1 /K for 20 and 30 passes of printed h-BN is suggestive of thermally stable h-BN after annealing. All inkjet-printed graphene/h-BN/graphene capacitors were fabricated and the leakage current density, JLeakage, was measured to be ∼ 72 nA/mm 2, while the capacitance density was measured to be ∼ 2.4 µF/cm 2 . Finally, the influence of temperature, frequency, and light irradiation on the performance of graphene/h-BN-based capacitive structures were explored using capacitance density - voltage measurements. The ratio, Con /Coff, between the capacitance density in the illumination ON state, Con, and in the illumination OFF or dark state, Coff, was also calculated for the graphene/h-BN capacitor fabricated with 30 printing passes. The Con /Coff was ∼ 1.6 at 6 K and ∼ 1.4 at 350 K (measured at 1 kHz frequency), suggesting the potential of this 2D graphene/h-BN heterostructure to serve as a photo-capacitive sensing element for printed electronics applications over a wide thermal regime from 6 K to 350 K. Graphical Abstract: Image, graphical abstract